2015
DOI: 10.1080/01140671.2015.1015576
|View full text |Cite
|
Sign up to set email alerts
|

Field evaluation of the effectiveness of mesh crop covers for the protection of potatoes from tomato potato psyllid

Abstract: Tomato potato psyllid (TPP; Bactericera cockerelli) is a serious pest of solanaceous crops in New Zealand. Control of TPP is currently dominated by synthetic biocides, although this method is curative and does not always prevent transmission of TPP-vectored plant diseases. This study evaluated mesh crop covers as non-chemical alternatives for controlling TPP in potato crops. Over two growing seasons in Canterbury, New Zealand, potatoes growing under mesh covers were found to have reduced numbers of TPP nymphs … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 38 publications
0
9
0
Order By: Relevance
“…That adults did not penetrate mesh, but newly hatched nymphs did, suggesting a means by which aphids entered all mesh covered plots in the field trial of Merfield (2017) : adult aphids that alighted on the upper surface of the mesh, produced nymphs, which are small enough to penetrate the mesh, and once through that they can reproduce on the potato crop. This result needs to be verified under field conditions.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…That adults did not penetrate mesh, but newly hatched nymphs did, suggesting a means by which aphids entered all mesh covered plots in the field trial of Merfield (2017) : adult aphids that alighted on the upper surface of the mesh, produced nymphs, which are small enough to penetrate the mesh, and once through that they can reproduce on the potato crop. This result needs to be verified under field conditions.…”
Section: Discussionmentioning
confidence: 99%
“…Talekar, Su & Lin (2003) and Licciardi et al (2007) reported that adult female moths of the armyworm ( Spodoptera littoralis (Boisduval 1833)) laid eggs on the top of a hooped screen, and the newly hatched larvae were sufficiently small to penetrate the mesh and drop onto the crop below. Merfield (2017) found a large number of lacewings ( Micromus tasmaniae (Walker 1860)) in plots of potatoes under mesh, following aphid outbreaks under the mesh. Lacewing adults are much too large to penetrate mesh, and the mesh was dug into the soil preventing entry from the edges, so it was hypothesised that the lacewings laid eggs on the mesh, and then the neonate larvae penetrated the mesh.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations